Financing Strategy Analysis to Maximize Company's Value Case Study: PT ABC (The Indonesian Journal of Business Administration, 2013)
As a newly born mining company, PT. ABC needs more funding to finance the capital expenditure. The capital expenditure is needed in order to ramp up the company production capacity. The current 0.5 Million Ton 2012 production cannot meet their target capacity which is 2.3 Million Ton. So, they need the additional funds to finance the capital expenditure immediately. The fund needed is approximately 5 Millions USD.There are two source of funding alternatives, which are internal and external sources. The internal source which is retained earnings is not possible due to the insufficient funds. The possible external sources are bank loan and advance from customer. So, there are three possible forms of financing alternatives for PT. ABC, which are bank loan, advance from customer and the combined of both bank loan and advance from customer. The concern for the company is they have a plan to become publicly traded company in near future, so this immediate financing need should be aligned with the company medium and long term plan. The parameter that needs to be analyzed from every alternative is the impact on company value. The company value of every alternative is analyzed using DCF (Discounted Cash Flow) method and Relative valuation method. Based on the analysis using DCF and Relative valuation method, the best possible alternative is the combined of both bank loan and advance payment. That alternative resulted in the highest equity value which ranged between Rp 2,421 Billions to Rp 3,556 Billions.Keywords: Funding Alternatives, Discounted Cash Flow Valuation, Relative Valuation